FACTORS INFLUENCING THE DEVELOPMENT OF MULTI DRUG-RESISTANT TUBERCULOSIS: LITERATURE REVIEW - Azzahra, Ilya Nur Aulia; Adi, Mateus Sakundarno; Hadisaputro, Suharyo (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2025)
Multidrug-resistant tuberculosis (MDR-TB) poses a significant challenge in global TB control, caused by Mycobacterium tuberculosis strains resistant to first-line antibiotics isoniazid and rifampicin. According to WHO, an estimated 400,000 MDR-TB cases were reported worldwide in 2024. This literature review aims to analyze socio-demographic, comorbidity, lifestyle, and policy factors influencing MDR-TB occurrence by reviewing 20 studies conducted in Africa, Asia, Europe, Australia, and America. Employing a meta-analysis approach, the study identifies key risk factors, including medication non-adherence, history of diabetes mellitus (DM) and HIV comorbidities, and productive age. Findings highlight the importance of targeted community interventions, improved treatment adherence, and strengthened TB control programs. Evidence-based policies for early screening and integrated management, as well as adaptive intervention models, are necessary. Further research is recommended to evaluate community-based approaches and digital innovations in enhancing treatment success.